2014
DOI: 10.1158/1541-7786.mcr-14-0184
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Expression of Cystathionine β-Synthase Promotes Glioma Tumorigenesis

Abstract: Cystathionine β-synthase (CBS) catalyzes metabolic reactions that convert homocysteine to cystathionine. To assess the role of CBS in human glioma, cells were stably transfected with lentiviral vectors encoding short hairpin RNA (shRNA) targeting CBS or a non-targeting control shRNA and subclones were injected into immunodeficient mice. Interestingly, decreased CBS expression did not affect proliferation in vitro but decreased the latency period prior to rapid tumor xenograft growth after subcutaneous injectio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
45
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 21 publications
8
45
0
Order By: Relevance
“…1B). It must be pointed out, nevertheless, that in a glioma model, CBS silencing increased, rather than decreased tumour growth, 148 illustrating the different tumour-cell-type dependent roles of H 2 S. Notably, because CBS activity affects the cellular levels of cysteine and homocysteine and modulates oxidative status, the biological effects of CBS inhibition or silencing cannot be simply equated to the pharmacological inhibition of H 2 S production. 149 Moreover, the pharmacological effects of the most commonly used CBS inhibitor, AOAA, go well beyond CBS inhibition.…”
Section: Hydrogen Sulfidementioning
confidence: 99%
See 1 more Smart Citation
“…1B). It must be pointed out, nevertheless, that in a glioma model, CBS silencing increased, rather than decreased tumour growth, 148 illustrating the different tumour-cell-type dependent roles of H 2 S. Notably, because CBS activity affects the cellular levels of cysteine and homocysteine and modulates oxidative status, the biological effects of CBS inhibition or silencing cannot be simply equated to the pharmacological inhibition of H 2 S production. 149 Moreover, the pharmacological effects of the most commonly used CBS inhibitor, AOAA, go well beyond CBS inhibition.…”
Section: Hydrogen Sulfidementioning
confidence: 99%
“…Indeed, there are several reports of: increased circulating and exhaled NO levels in patients with cancer; 182,183 increased carboxyhaemoglobin levels in colon cancers; 184 and increased exhaled H 2 S levels in patients with cancer (reviewed in 148 ).…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…When subcutaneously or orthotopically injected into the flank of SCID mice, the subclone with CSE silencing exhibited a shorter latency period for tumor growth, as well as a more pronounced overall tumor growth rate. In addition to greater tumor volume, the CBS silenced tumors exhibited increased depth of invasion, vascular density, cell proliferation, and more apoptosis (Takano et al 2014). These findings unveil a role of CBS in glioma that is markedly different from its role in colon cancer or ovarian cancer.…”
Section: Cbs Silencing Accelerates the Development Of Gliomamentioning
confidence: 99%
“…These findings unveil a role of CBS in glioma that is markedly different from its role in colon cancer or ovarian cancer. As far as the mechanisms responsible for the observed effects, in vitro studies by Takano and colleagues showed that glioma cells respond to CBS silencing with increased VEGF and ANGPTL4 levels, higher HIF2a expression and increased anchorage-independent cell growth (Takano et al 2014). …”
Section: Cbs Silencing Accelerates the Development Of Gliomamentioning
confidence: 99%
“…Currently, there is a resurgence of interest in enzyme-mediated amino acid deprivation as a new therapeutic approach for cancer treatment. 6,7,21,22 For example, arginine depletion can inhibit tumor cell proliferation and induce cell death pathways. Here we endeavor to provide a basic understanding of the roles of arginine in normal and tumor cell with emphasis on current knowledge and developments in the application of enzyme-mediated arginine-depriving therapy as a potential anti-cancer approach.…”
Section: Introductionmentioning
confidence: 99%